Safety and effectiveness of angiotensin receptor-neprilysin inhibitors in Indian patients with heart failure with preserved ejection fraction – “ARNI-PRESERVED” study - Pankaj Jariwala; Arshad Punjani; Harikishan Boorugu; Dilip Babu Madhawar; Kartik Jadhav (Heart India, 2021)
Background: The goal of this study is to look at the safety and efficacy of angiotensin receptor-neprilysin inhibitors (ARNI) (valsartan/sacubitril), a combination of angiotensin II receptor blocker and neprilysin inhibitor ARNI, in patients with heart failure with preserved ejection fraction (HFpEF). Materials and Methods: Between June and December 2020, retrospective research was conducted on a study participant of primarily angiographically confirmed computer-aided design patients who underwent complete revascularization. A total of 154 HFpEF patients (87 females and 67 males) were treated with ARNI, which was subsequently titrated up to a maximum tolerable dose and monitored in an outpatient clinic. Fifty-six patients were given ARNI while in the hospital for decompensated heart failure before being discharged. Results: Patients were categorized as the New York Heart Association (NYHA) class III (71.4%) and NYHA class II (28.6%). Diabetes mellitus was identified in 52% of patients, while hypertension was found in 78%. Symptomatic clinical improvement was observed, with a substantial decrease in NYHA class down to NYHA class II (P = 0.018). A considerable decrease in NYHA class resulted in symptomatic clinical improvement as well as the rales and peripheral edema had resolved (P < 0.001). The NT-pro-BNP levels were considerably lowered (P < 0.001). The echocardiographic parameters for diastolic function (E/A, E/E' ratios) improved. In individuals with HFpEF, ARNI resulted in significant clinical benefits. Conclusion: In individuals with HFpEF, sacubitril/valsartan, ARNI resulted in significant clinical benefits. A randomized research is also required to see if it results in beneficial outcomes for a wider sample.